Low temperature fluidized bed nitriding of austenitic stainless steel - Haruman, E.; Sun, Y.; Malik, H.; Sutjipto, A.G.E.; Mridha, Shahjahan; Widi, K. (2006)
In the present investigation, low temperature nitriding has been attempted on AISI 316L austenitic stainless steel by using a laboratory fluidized bed furnace. The nitriding was performed in temperature range between 400°C and 500°C. X-ray diffraction, metallography, and corrosion tests were used to characterize the resultant nitrided surface and layers. The results showed that fluidized bed process can be used to produce a precipitation-free nitrided layer characterized by the S phase or expanded austenite on austenitic stainless steel at temperatures below 500°C. But there exists a critical temperature and an incubation time for effective nitriding, below which nitriding is ineffective. The corrosion behaviour of the as-nitrided surfaces is significantly different from that previously reported for low temperature plasma nitriding. This anomaly is explained by the formation of iron oxide products and surface contamination during the fluidized process.